Does magnesium chloride modify aldrin-induced neurotoxicity in rats? - Lazarini, Carlos Alberto; Vassilieff, Igor [UNESP] (My University, 1998)
Magnesium chloride (MgCl2) has been proposed for the treatment of seizures of different etiologies. The present study investigated the effect of MgCl2 on aldrin-induced seizures. Initially, 50 male rats received 60 mg aldrin/kg po and the effects were classified as muscular twitches, clonic convulsions or tonic-clonic convulsions. Another group of 40 rats dosed with 60 mg aldrin/kg po received 0, 4, 8, or 12 mg MgCl2/kg im. The percentage of tonic-clonic convulsant rats that resulted from MgCl2 treatment were 90% at 0 mg/kg; 50% at 4 mg/kg, 40% at 8 mg/kg and 20% at 12 mg MgCl2/kg. The percentage of survivors in the group receiving 12 mg MgCl2/kg was 80% while the control group had 20% survival. The clonic convulsions were not modified by MgCl2 treatment. Blood and brain concentrations of aldrin and dieldrin (metabolite of aldrin) did not differ among groups. The MgCl2 administration decreased the neuroexcitability induced by aldrin and increased survivability.
Keywords: aldrin; magnesium chloride; animal experiment; anticonvulsant therapy; brain level; controlled study; drug effect; male; neurotoxicity; nonhuman; rat; seizure; Aldrin; Animals; Behavior, Animal; Drug Interactions; Insecticides; Magnesium Chloride; Male; Rats; Rats, Wistar; Seizures; Animalia